Path coefficient and stability analysis studies in andigena potato - RAJKUMAR, RAJKUMAR; KANG, G S (The Indian Journal of Agricultural Sciences, 2013)
The relationship between yield and some measures of growth and yield was examined during 1995-97 for andigcna potatoes (Solanum tuberosum) grown in 3 different nutritional environments,viz 120 kg N: 35.2 kg P: 83.0 kg K/ha; 150 kg N: 44.0 kg P: 103.7 kg K /ha and 180 kg N: 52.8 kg P; 124.4 kg K/ha. Consistent association of characters across 3 environments were consideredÂ for drawing conclusions. Tuber yield was positively and significantly correlated with haulm weight, lcaf area index and mean tuber weight, Leaf area index was positively correlated with mean tuber weight, tuber number and tuber yield. Tuber number was negatively correlated to mean tuber weight. Mean tuber weight proved tom be the most important determinant of tuber yield. Mean tuber weight and number of tuber had significant and positive direct effect on tuber yield. The number of tuber, however, had significant and negative indirect effect on tuber yield via mean tuber weight. Leafarea index had significant and positive indirect effect on tuber yield via mean tuber weight. out of the 30 genotypes evaluated for tuber yield at 90 days harvest,genotypes ’JEX/A 30’, ’JEX/A 199’, ’JEX/A 318’, JEX/ A 459’, ’JEX/A 541’, ’JEX/A 715’, ’JEX/A 717’, ’JEX/A 764’, ’JEX/A 1102’, ’JEX/A 1152’ and ’JEX/B 998’ was found to be highly stable for tuber yield. These genotypes can be gainfully used in andigena breeding programme.